Laboratory study of toxicity or tolerance of CCA preservative and heavy metal constituents copper, chromium and arsenic to Malaysian tropical fungi - Wong, Andrew H.H; Venas, Thomas Mark; Morsing, Niels; Tan, Clarence C.L.; Chong, Peter Kian Fui (IRGWP, 2011)
CCA preservative and its constituent heavy metal tolerance and toxicity to 3 Malaysian isolates Phialophora fastigiata (soft rot fungus), Paecilomyces variotii (mould fungus) and an unidentified white rot Basidiomycete, was investigated by the modified ‘Strange-Smith’ agarwell- plate technique with 1.6% CCA concentration and the malt-agar-plate bioassay technique with a range of CCA and constituent metal salt concentrations of 0.0024 – 5%m/m. Daily linear hyphal extension was measured between 6 and 22 days depending on relative fungal growth rates. The slow growing Phialophora fastigiata sustained mean daily hyphal growth (mm) at relatively higher concentrations of CCA preservative (toxic limits: 0.24 – 0.48%m/m) and their heavy metal constituents (copper-salt: 5.0 – 10.0%m/m; chromium-salt: 0.076 – 0.24%m/m) than the faster growing mould isolate Paecilomyces variotii (CCA: 0.019 – 0.076%m/m; chromiumsalt: 0.076 – 0.24%m/m) and the white rot Basidiomycete of intermediate growth rate (CCA: 0.076 – 0.24%m/m; copper-salt: 0.076 – 0.24%m/m; chromium-salt: 0.0095 – 0.019%m/m) except for arsenic-salt (Phialophora fastigiata: 0.076 – 0.24%m/m; Paecilomyces variotii: 0.48 – 0.95%m/m; Basidiomycete: 0.24 – 0.48%m/m). The results showing varying efficacies (toxicity versus tolerance) in vitro of CCA and their metal constituents between these fungi can have implications to ground-contact wood protection capabilities of CCA.